2010
DOI: 10.1097/qai.0b013e3181d0558f
|View full text |Cite
|
Sign up to set email alerts
|

Improved Detection of CXCR4-Using HIV by V3 Genotyping: Application of Population-Based and “Deep” Sequencing to Plasma RNA and Proviral DNA

Abstract: Triplicate analyses of V3 standard sequence data detect greater proportions of CXCR4-using samples than previously achieved. Sequencing proviral DNA and "deep" V3 sequencing may also be useful tools for assessing tropism.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
66
1

Year Published

2011
2011
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(70 citation statements)
references
References 24 publications
3
66
1
Order By: Relevance
“…Phenotypic assays usually involve the generation of patientderived env recombinant viruses to determine their ability to infect reporter cell lines expressing HIV-1 receptors and coreceptors (16)(17)(18), while others are based in the quantification of cell-to-cell fusion events (19,20). On the other hand, genotypic tests based on population (12,14,21) or deep sequencing (22)(23)(24) take advantage of the association of certain regions in the env gene as determinants of CCR5 or CXCR4 tropism, mainly in the V3 region of the gp120, and their interpretation based on a series of algorithms and bioinformatic tools to infer the ability of HIV-1 to use any or both coreceptors to enter host cells (25)(26)(27)(28). As expected, both approaches have advantages and disadvantages, but particular emphasis has been made on their sensitivity to detect minor non-R5 variants, turnaround time, and, more important, their accuracy to determine HIV-1 coreceptor tropism (12,14,29).…”
mentioning
confidence: 99%
“…Phenotypic assays usually involve the generation of patientderived env recombinant viruses to determine their ability to infect reporter cell lines expressing HIV-1 receptors and coreceptors (16)(17)(18), while others are based in the quantification of cell-to-cell fusion events (19,20). On the other hand, genotypic tests based on population (12,14,21) or deep sequencing (22)(23)(24) take advantage of the association of certain regions in the env gene as determinants of CCR5 or CXCR4 tropism, mainly in the V3 region of the gp120, and their interpretation based on a series of algorithms and bioinformatic tools to infer the ability of HIV-1 to use any or both coreceptors to enter host cells (25)(26)(27)(28). As expected, both approaches have advantages and disadvantages, but particular emphasis has been made on their sensitivity to detect minor non-R5 variants, turnaround time, and, more important, their accuracy to determine HIV-1 coreceptor tropism (12,14,29).…”
mentioning
confidence: 99%
“…A clinical proof for the validity of this exclusion is not available, and tropism changes between screening and baseline in the clinical studies may reflect the test variability or a certain instability of the viral tropism (50)(51)(52). Recent deep-sequencing analyses have demonstrated that low proportions of X4-tropic viruses can be found in almost any clinical sample, yet the clinical relevance, e.g., of X4-tropic virus minorities below 2% in a given virus population found in clinical specimens remains unclear (53).…”
Section: Resultsmentioning
confidence: 99%
“…Recent massive parallel sequencing also detected minor X4 populations at a higher frequency compared to ESTA. [19][20][21] Additionally, the presence of basic amino acids at codons 11, 24, or 25 does not guarantee that the variant will use CXCR4 efficiently enough to be detected using a culture-based assay. Given that HIV-1 utilization of CXCR4 evolves over time, 1,9 genotypic, but not phenotypic, assays can potentially detect viruses that have begun the evolutionary process toward use of CXCR4.…”
Section: Discussionmentioning
confidence: 99%